Hairy Indigo Control in Peanut - Jason Ferrell; Blaire Colvin; Ramon Leon (EDIS, 2015)
Hairy indigo is an annual legume that was introduced to Florida as a forage crop. It has since escaped cultivation and can be a troublesome weed in some crop settings, particularly in peanut production, since we are attempting to control a legume weed in a legume crop. This 2-page fact sheet was written by Jason Ferrell, Blaire Colvin, and Ramon Leon, and published by the UF Department of Agronomy, March 2015. (Photo by Blaire Colvin, UF/IFAS)